Terpyridine derivatives functionalized with (hetero)aromatic groups and the corresponding Ru complexes: Synthesis and characterization as SHG chromophores. (March 2018) - Fernandes, Sara S.M.; Belsley, Michael; Ciarrocchi, Carlo; Licchelli, Maurizio; Raposo, M. Manuela M.
Abstract: Push–pull terpyridine derivatives3 were synthesized and characterized in order to study the variations produced in their optical and electronic properties by linking different (hetero)aromatic electron donor moieties at 4′-position of the electron deficient terpyridine moiety. The final donor-acceptor systems3a-g were synthesized in fair to good yields by Kröhnke condensation of the precursor aldehydes1, with 2-acetylpyridine2 . Hyper-Rayleigh scattering in dioxane solutions using a fundamental wavelength of 1064 nm was employed to evaluate their second-order nonlinear optical properties. Terpyridine derivative3g functionalized with the 9-ethyl-9 H -carbazolyl group exhibited the largest first hyperpolarizability ( β = 610 × 10 −30 esu, using the T convention) thus indicating its potential application as a second harmonic generation (SHG) chromophore. Terpyridine derivatives3 were also used as ligands for the synthesis of novel [Ru II (tpy)(NCS)3 ] – complexes, prepared in good yields by a two-step procedure involving the preparation of [Ru III (tpy)(Cl3 )] as intermediates. Ruthenium II complexes display a broad absorption in the visible range, accounting for their very dark color. Their redox behaviour is mainly characterized by the Ru II -Ru III oxidation and by the ligand-centered reduction, whose potentials can be finely tuned by the electronic properties of the aromatic substituents on the terpyridine ligand. Hyper-Rayleigh scattering in methanol solutions using a fundamental wavelength of 1064 nm was also employed to evaluate their second order nonlinear optical properties. Graphical abstract: Highlights: Synthesis of terpyridines functionalized with (hetero)aromatic groups and the corresponding Ru complexes. Study of redox and optical properties of terpyridine derivatives and the corresponding Ru complexes. Influence of different π-spacers linked to terpyridine moiety in the optical and redox properties of ligands and Ru complexes. Evaluation the second-order nonlinear optical properties using Hyper-Rayleigh scattering technique.